Analyzing the Content of English Language Textbook for the Sixth Elementary Grade in the Kingdom of Saudi Arabia in Light of Multiple Intelligences Theory - Alfaisal, Amani Abdullah Hamad; Al-Kaltham, Maha Ibrahim (Journal of Curriculum and Teaching Methodology, 2023)
The current research sought to explore the availability of multiple intelligences in the sixth-year English textbook. To meet such an end, the researcher adopted the descriptive analytical approach with the content analysis technique. Two instruments were developed, namely the multiple intelligences Inventory available in the sixth-year English textbook, and the second instrument was the content analysis checklist to analyze the contents of the sixth-year English textbook (three parts through three semesters). The results of the research revealed that the availability of verbal-linguistic intelligence in the English course was high. While the availability of mathematical-logical intelligence, visual-spatial intelligence and intrapersonal intelligences were at an average degree. However, the availability of bodily-kinesthetic, musical, naturalistic and interpersonal intelligences appeared in small degrees. Furthermore, there were no statistically significant differences in the degree of availability of multiple intelligences in the English textbook in the semesters (first, second, and third). In light of these results, the researcher recommended the need for the availability of the eight multiple intelligences - revealed by the current study - in the cognitive content of the English language textbook in a way that achieves a balance between the content and the multiple intelligences.